Structural transformation-induced surface strengthening of borosilicate sealing glass for solid oxide fuel cells. Issue 12 (15th August 2019) - Yan, Jiajia; Wu, Yukun; Lin, Dewei; Zhan, Hongbing; Zhuang, Haiyan; Sa, Baisheng; Zhang, Teng
Abstract: In solid oxide fuel cells (SOFCs), it is important that the sealing glass has adequate mechanical strength (rigidity) to withstand stack loads while simultaneously having appropriate resiliency to release the internal stress and thus resist cracking. However, at present, sealing glass is either resilient or rigid. Animal teeth exhibit a bilayer structure that combines remarkable surface hardness to withstand mastication loads with the high resiliency of the inner layer to resist crack propagation. Drawing from this, in this study, we selected a heat-treatment temperature of 700 °C to simulate the operating temperature of the sealing glass and SOFCs, and carried out experimental and theoretical investigation of a typical borosilicate sealing-glass system. The results revealed that surface strengthening occurs within 200 nm depth as the heat-treatment time increases; that is, there is a gradient change in the mechanical property from the surface to the interior of glass, indicating that the surface has greater hardness and elastic modulus to bear stack loads, while the interior has better resiliency and may help resist crack initiation and propagation. A possible mechanism for this strengthening is proposed. The 4-coordinated B and Al centred BO4 and AlO4 can form a glass network structure with SiO4 (i.e., B–O–Si, Al–O–Si), which may lead to surface strengthening due to the increase in the degree of network crosslinking.